Estratégias de marketing e vendas: um estudo de caso em uma empresa de cosméticos situada no município de Parintins- Am - Barros, Yanna Karen de Oliveira (Brasil, 2022)
This work has as main approach the marketing and sales strategies in the organizational scope. In order to solve the problem related to the theme, the general objective was elaborated: to analyze the marketing strategies used by a cosmetics company in the sales of its products to obtain a competitive advantage in the local market. The methodology of this study is based on quantitative-qualitative research, using field research and case studies as a method of procedure. The instruments used in data collection were the standardized interview and the questionnaire in Google form format. The results demonstrate that the marketing and sales developed in the company are satisfactorily aligned. This is due to the following aspects: structure and environment, quality and variety of products, such as beauty, personal hygiene and perfumery, customer service, and the dissemination of their products through social networks, reaching a greater number of customers, both those residing in the same neighborhood, as they live in other locations. In this way, it is concluded that the investigated company has a considerable competitive advantage to the detriment of the effectiveness of several fundamentals of the Marketing mix, directly influencing the increase of its sales and the loyalty of its customers